ESTIMATION OF SHORTENING BETWEEN THE SIBERIAN AND INDIAN PLATES SINCE THE EARLY CRETACEOUS - Li P.; Cui J.; Li L.; Gao R. (My University, 2002)
A comparative study of the amount of latitudinal shift of the Siberian Plate, the Lhasa Block, the Himalayan Block and the Indian Plate using palaeomagnetic data shows that the Himalayan Block belongs to the Indian Plate. The Neo-Tethys Ocean, which separated the Himalayan and Lhasa Blocks, opened to its greatest width of 31.9° in latitude in the Early Cretaceous. The extent of shortening of the latitudinal distance between the Siberian and Indian Plates amounts to 58.2° since the Early Cretaceous. It was found that after the determination of the greatest width of Neo-Tethys Ocean, the latitudinal shortening of the crust between the Indian and Siberian Plates reached 26.3°, or about 2760km. On the basis of the palaeomagnetic data obtained from the Qaidam Block, the latitudinal shortening between the Himalayan and Qaidam Blocks reached 50.2° since the Early Cretaceous. It was concluded that over the past 50Ma, since the Early Cretaceous, the latitudinal shift of the southern blocks or plates was larger than that of the northern ones, and that shortening between the Qaidam and Himalayan blocks was greater than the shortening between the Qaidam Block and the Siberian Plate. This differential latitudinal movement is the main cause of convergence, resulting in the compression and uplift of the Qinghai-Tibetan Plateau.
Keywords: LATITUDINAL SHIFT; THE HIMALAYAN BLOCK; COMPRESSION; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая